Modeling of Hybrid Fiber Optic and Free-Space Optical Communication Systems - Evran, Serap Kilinc; Unverdi, N. Özlem (IEEE, 2023)
Free-space optical (FSO) communications systems have many advantages, such as large bandwidth, high data transmission rate, low cost, and easy installation process. In this study, a hybrid system incorporating both wired optical communication and free-space optical communication was designed, and its performance was analyzed. OptiSystem 20.0 simulation program was utilized in designing and performance evaluation of the hybrid communication system.
Keywords: Communication technologies; fiber optic communication; free-space optical communications; laser; amplifier; Computer Science; Communication; Engineering; Telecommunications